Efficient keyword search using encrypted text in grid computing architecture. (2016) - Gomathi, S.; Manimegalai, D.
Searching needs effective key-based cryptographic algorithms. The retrieval of encrypted data from huge set of distributed databases leads to complexity. This study is based on certain set of keywords. Most of the key-based cryptographic algorithms are more effective but each and every algorithm has its own limitations. Sometimes, there arises a huge need to direct the data to grid computing system in the cryptic form. No algorithm in an intelligible form has been made available to the intruders. Complexity and computational overhead attached with these algorithms make the retrieval task more complex and ineffective. To overcome these problems, it is proposed to introduce a novel keyword search technique in the grid computing environment. The result so obtained in keyword search using this novel technique was most effective and with the reduction of retrieval time in the grid computing environment.